Grafted tubularised incised plate: A right option in the management of failed mid-penile and distal hypospadias - Rajendra B Nerli; Shoubhik Chandra; Shreyas Rai; Neeraj S Dixit (Wolters Kluwer Medknow Publications, 2023)
Introduction: Hypospadias is a common congenital anomaly of the urogenital system. The goal of the initial repair is to correct any curvature, ensuring that the penis is straight, allowing for successful intercourse, to create a functional neourethra to direct the urinary stream in a forward direction and to produce a cosmetically normal-appearing penis with a slit-like meatus at the tip of the glans. Failures and complications do occur. Failed hypospadias repair is often associated with penile skin loss or deficient local tissue, which leaves the penis short, scarred and hypovascular. Repair of a failed hypospadias surgery represents one of the most challenging and difficult tasks. We retrospectively evaluated our series of children who underwent reoperative grafted tubularised incised plate (G-TIP) repair for a mid-penile or distal penile hypospadias. Materials and Methods: With permission obtained from the university/institutional ethics committee, we retrospectively reviewed the inpatient and outpatient records of all children ≤18 years of age who underwent a reoperative G-TIP hypospadias repair. Results: During the study period, a total of 22 children (mean age: 6.8 years) underwent reoperative G-TIP repair. The mean number of previous repairs was 1.36. Nine (40.9%) of the children had persisting chordee. Complications were noted in five (22.7%) children. Conclusion: G-TIP is a good option in the management of mid-penile or distal penile failed hypospadias repairs. Although complications are noted, they are easily manageable.